Enough potential repudiation: Economic and legal aspects of sovereign debt in the pandemic era - Anna Gelpern; Ugo Panizza (Graduate Institute of International and Development Studies, 2022)
This paper surveys recent economic and legal literature on sovereign debt in light of the COVID-19 shock. Most of the core theoretical contributions we review across the two disciplines hinge on immunity, and the sovereign borrower's consequent inability to commit to repay foreign creditors, as the distinguishing attribute of sovereignty. We highlight a persistent gap between sovereign debt theories grounded in immunity and empirical evidence that low- and middle-income country governments borrow far more than theory would predict. On the other hand, advanced economy governments, generally viewed as outside the scope of this literature before the euro area debt crisis, have shown themselves to be far more commitmentchallenged than previously supposed. We conclude that the traditional split between a literature concerned with developing economy sovereigns that repudiate, and one concerned with advanced economies that don't, is no longer appropriate (if it ever was). We argue that shifting some attention away from immunity to a different attribute of sovereignty-authority, or the ability to make rules for domestic markets and negotiate market access terms with other sovereigns-could help bridge the gap between the two literatures, and between theory and experience.
Keywords: F30; F34; G15; K12; 330; Sovereign Debt; Sovereign Default; Public Debt